PENGARUH MEDIA TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (ALLIUM ASCALONICUM L.) - Jasmi; Izwar (Jurnal Bionatural, 2024)
Planting media plays an important role in providing nutrients and water needed by plants to grow. Each type of plant requires certain criteria for its planting media. Plant varieties are a group of plants of a type or species characterized by plant shape, plant growth, leaves, flowers, seeds and expression of genotype characteristics. This study aims to determine the effect of planting media on growth and yield of shallot varieties (Allium ascalonicum L.). This research was conducted at the experimental garden of the Faculty of Agriculture, Teuku Umar University, Meulaboh, West Aceh from February to April 2024. The materials used were the type of bima shallot seeds and crown varieties, alluvial soil, sand, peat soil with a combination of manure. This study used a factorial randomized block design (RAK). The first factor is the planting media consisting of three treatment levels, namely M₁: alluvial planting media, M₂: peat planting media and M₃: sand planting media + alluvial soil. The second factor is the shallot variety consisting of two levels, namely B₁: crown variety and B₂: bima variety. The parameters observed were plant height, number of leaves, number of bulbs, wet and dry weight of bulbs. The results of the F test of the analysis of variance showed that the treatment of planting media had a very significant effect on plant height, number of leaves, number of bulbs and dry weight of bulbs